Conversion Chemistry: Colloids of Holey Gd2O3 Nanosheets Converted from Exfoliated Gadolinium Hydroxide Layers (Small 36/2018). Issue 36 (6th September 2018) - Jeon, Ki‐Wan; Zhang, Luojiang; Choi, Seonyeong; Lee, In Su
Abstract : In article number1802174, In Su Lee and co‐workers describe a confined conversion approach with exfoliated gadolinium hydroxide layers at high temperatures within a silica nanoshell that produces a colloidal suspension of holey Gd2 O3 nanosheets that feature a highly 2D‐anisotropic morphology with a few‐nanometer thickness and a unique in‐plane mesoporosity. The resultant suspension allows for the fabrication of porous and crystalline Gd2 O3 thin films through wet‐coating deposition methods.